Kælkebakker, ambulancer og brandvagter. Sophus Falck og hans kamp for at kommercialisere redningstjenesten - Mandel Refskou, Morten (Historisk Tidsskrift, 2013)
Sophus Falck and His Struggle to Commercialize Emergency Rescue Services in DenmarkDenmark is one of the relatively few countries where private companies provide emergency rescue and fire-fighting services. The principal Danish firm in this specialized service industry is the Falck Rescue Corps (Falcks Redningskorps), founded by Sophus Falck in 1906. The present article, which presents an analysis of Falck's entrepreneurship and his struggle to establish the company, is divided into two main parts: first, a brief survey of the dominant trends in the field of entrepreneurship research; second, an empirical study of Falck's entrepreneurial activity. The survey of entrepreneurial research shows that the pre-eminent theory of the field was developed by Joseph Schumpeter more than ninety years ago. Although Schumpeter himself as well as many others have revised the premises and scope of the theory, its basics remain inescapably at the core of even the most recent research. Because of the theory's durability and insights, and because its typology of entrepreneurial behaviour is well suited to empirical research, Schumpeter's typology is used as the basis of analysing Falck's activities. A close scrutiny of Falck's entrepreneurial behaviour reveals a highly dynamic and innovative personality who was particularly deft at adapting his business enterprises to the changing societal environment. His persistence came to the fore in his hard-headed struggle to transform his idea of a rescue business into a marketable service. Moreover, he evidenced a persistent ability to think up new product schemes and envisage new potential markets. His establishment of the Rescue Corps fits him neatly into Schumpeter's typology of the entrepreneur. By way of conclusion the study notes that the use of a solid theory of entrepreneurship in an empirical test of Falck's business behaviour has contributed to a more multi-faceted and subtle picture of one of Denmark's most celebrated entrepreneurs. At the same time it emphasizes that Falck's rescue corps was first and foremost a business, not a benevolent society. Translated by Michael Wolfe